Equality in Kenya's 2010 constitution : understanding the competing and interrelated conceptions - Miyandazi, Victoria, 1989- (Oxford, UK ; Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This book asks whether there is a coherent conception of equality in Kenya's 2010 Constitution and explores how competing and interrelated ideas of equality in it should be conceptualised, interpreted and applied. Making a significant contribution to the ongoing global conversations on the various understandings of equality, the book illuminates the many ways in which diverse equality guarantees clash, or are interrelated. It also sets out principled approaches on how they can be coherently interpreted to address the myriad inequalities in Kenya. Taking a comparative approach, the book considers how other jurisdictions including the United States, the United Kingdom, Canada, South Africa, India and Botswana have approached the conceptualisation, interpretation and application of various equality concepts. The book focuses on important issues such as: - transformative constitutionalism in relation to the interpretation of Kenya's 2010 Constitution; - expanding the list of enumerated grounds for non-discrimination; - affirmative action; - accommodating religious and cultural diversity versus gender equality; - the interrelation between socio-economic rights and status-based equality"--
Introduction -- Interpretation of Kenya's 2010 Constitution -- Multiple and competing conceptions of equality -- Grounds for non-discrimination -- Conceptualisation and application of affirmative action -- Competing equalities : religion, culture and gender equality -- The interrelationship between socio-economic rights and status-based equality -- Interrelationship between socio-economic rights and status-based equality in current Kenyan jurisprudence -- Conclusion : finding harmony.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Equality before the law -- Kenya; Human rights; Discrimination -- Law and legislation -- Kenya; Constitutional law -- Kenya; Electronic books